The Unravelled Link between Chronic Kidney Disease and Hepatitis C Infection. (2nd July 2014) - Fabrizi, Fabrizio; Messa, Piergiorgio; Martin, Paul
Abstract : The 2011 report of the World Health Organization General Assembly on noncommunicable diseases identified chronic kidney disease as a worldwide health issue posing a heavy economic burden. Hepatitis C virus infection, which is responsible for over 1 million deaths resulting from cirrhosis and liver cancer, is linked to chronic kidney disease in several ways; some forms of renal disease are precipitated by hepatitis C and patients with end-stage chronic renal disease are at increased risk for acquiring HCV. The aim of this review is to update the evidence on the relationship between hepatitis C infection and chronic kidney disease. Information has been accumulated in the last decade indicating that HCV plays an adverse effect on the incidence and progression of chronic kidney disease; a novel meta-analysis of observational studies (seven longitudinal studies; 890, 560 unique individuals) found a relationship between hepatitis C seropositivity and incidence of reduced estimated glomerular filtration rate (adjusted relative risk, 1.70; 95% CI, 1.20; 2.39;P = 0.002 ) in the adult general population. In addition to conventional risk factors, hepatitis C may be an additional factor for the development of chronic kidney disease, and an atheromasic activity of hepatitis C virus has been mentioned. The link between hepatitis C and atherosclerosis could also explain the excess risk of cardiovascular mortality that has been observed among hepatitis C virus seropositive patients undergoing maintenance dialysis. A number of biologically plausible mechanisms related to hepatitis C virus have been hypothesized to contribute to atherosclerosis. Implementation of effective treatment intervention towards hepatitis C is required to decrease the healthcare burden of hepatitis C and to prevent the progression of chronic renal disease.